Mechanisms for Changing the Structure of Mpumalanga Economy through Industrialization - Nkonyane, Nkosinathi Senzo; Mashau, Pfano (Journal of Economics and Behavioral Studies, 2017)
Industrialization is still viewed by many countries as a tool for achieving economic growth and development (Sampath, 2016). Almost all countries that have attained growth have followed an industrialization trajectory (Xu & van Leeuwen, 2016; Szirmai, 2012). Britain— with the introduction of the industrial revolution— and other countries that followed suit experienced unprecedented economic growth. This research explored the structure of Mpumalanga, a South African provincial economy, which was found to be inhibiting growth. Its aim was to suggest mechanisms for industrializing the province in order to attain growth and economic development. The methodology employed in this study involved interviews with members of the Mpumalanga Industry Sector Forum, representatives from big industry, business chambers, all three spheres of government, including State Owned Entities and Development Funding Institutions (FDIs). A total of 20 respondents were selected for the study. The method used was convenient for obtaining first-hand information on the state of industrialization in the province and for soliciting a new set of ideas, resulting in the recommendations of this study. The study discovered a number of factors that inhibited industrialization, including the unavailability of industrial infrastructure, the cost and difficulty of doing business and lack of skills and support for SMMEs. The study proposes the use of an Industrial Centres of Competence model that concentrates on certain industrial sectors with a suite of support services for industry, incubation and supplier development centres for small businesses, research and development, as well as innovation centres for industry.